A Rare Case of Prototheca Algaemia in a Patient with Systemic Lupus Erythematosus and Recent Belimumab Infusion - Carolina Mejia-Otero; Shelley Singh; Luis Arias Urdaneta; Carlos Sesin; Anindita Chakrabarti; Nanci Mae Miller; Claudio Tuda (Case Reports in Immunology)
Novel agents for the treatment of immune-mediated diseases such as systemic lupus erythematosus (SLE) have been increasingly used as an alternative to or in combination with conventional therapies. Belimumab, a human monoclonal antibody that inhibits B-cell activating factor (BAFF), has demonstrated efficacy in moderate-to-severe SLE with similar adverse effects when compared to other biologic agents and conventional SLE therapies. Here, we describe a woman with SLE and diabetes mellitus (DM) on immunosuppressive therapy for five years who was admitted to the hospital for pneumonia but had a complicated hospital course with multiple infections and, most notably, a nosocomial algaemia due to Prototheca wickerhamii, which was treated successfully with amphotericin B. She had recently received three belimumab infusions as an outpatient prior to admission to the hospital. To the best of our knowledge no cases of human protothecosis in patients receiving belimumab have been described in the English literature; however, unusual infections have to be considered in all patients undergoing immunosuppressive therapies who persist with fever despite conventional antimicrobials.